ANALISIS LAPORAN REALISASI ANGGARAN BELANJA PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA MEDAN - Penta Volina Silitonga (JEBIM Prima, 2022)
The research with the title Analysis of Budget Realization Reports at the Regional Financial and Asset Management Agency of Medan City aims to. determine the realization, growth, and level of efficiency of spending at the Regional Financial and Asset Management Agency (BPKAD) of Medan City. The type of data used in this study is secondary data, secondary data is data that is already available and collected by other parties. The data collection technique used in this research is to use the Documentation technique. Documents are records of events that have passed, documents can be in the form of writing, pictures, or monumental works of someone. Data analysis technique used in this research is descriptive analysis technique. The results show that BPKAD spending has the criteria for the preferred difference, the spending variance, which is showing the difference between the budget and the realization of spending, if the difference in the realization of spending is smaller than the budget, it means identifying the favorable variance or budget savings. Expenditure growth analysis is to find out the development of spending from year to year by comparing the realization of the budget from a certain year to the realization of the budget in the following year. BPKAD expenditure growth tends to increase every year. Budget efficiency is measured by means of a comparison between expenditure reactivation and the expenditure budget, the efficiency ratio is not absolute, but relative, the efficiency of BPKAD spending has been running very efficiently, quite efficiently, and efficiency